ENHANCING ORAL PRESENTATION SKILLS IN THE CLASSROOM OF A PUBLIC SCHOOL - Rapôso da Silva Ferreira, Gutemberg (Revista Gênero e Interdisciplinaridade, 2025)
The present article aims to explore the oral production of students in the public school system. Using an action-research approach, the study seeks to enhance the oral presentation skills of students in a classroom of a public school. The research was conducted during the English Language Festival (ELF) at the North Goiano Public School in Araguaína-TO, Brazil. The methodology included video recordings, observation lists, and student self-assessments. The analysis was carried out both qualitatively and quantitatively. The study was grounded by renowned authors in the field, such as McLaren (2019), Tuovinen and Sweller (1999), Zimmerman (2011), Braun and Clarke (2006), and Van Ginkel (2019). The results indicate that the intervention was successful, with 88% of students rating their oral presentations as satisfactory or very satisfactory. This suggests a significant improvement in their communication skills, self-confidence, and overall academic performance.